Comorbidities associated with eosinophilic chronic rhinosinusitis: A systematic review and meta‐analysis. (13th April 2020) - McHugh, Tobial; Levin, Marc; Snidvongs, Kornkiat; Banglawala, Sarfaraz M.; Sommer, Doron D.
Abstract: Objective: Eosinophilic chronic rhinosinusitis (ECRS) is a histological subtype of CRS that is generally recognised as being more difficult to manage. Patients with ECRS tend to have greater disease severity and poorer treatment outcomes after sinus surgery when compared with non‐ECRS patients. The histopathology and biomarker assessments of ECRS are often unavailable prior to surgery and may be impractical and costly to analyse. Thus, the primary objective of this study was to understand clinical comorbidities associated with ECRS. Design/Setting: We searched three independent databases for articles that reported clinical CRS comorbidities associated with tissue eosinophilia. Data from studies with the same reported comorbidities were pooled, and a forest plot analysis was used to assess potential associations with four different conditions including allergic rhinitis, ASA sensitivity, asthma and atopy. The association between the phenotype of nasal polyps and ECRS was also quantified as a secondary objective. ECRS cut‐off levels were as defined by papers included. Main outcome/Results: Eighteen articles were identified. The presence of nasal polyps (the first numbers in brackets represent odds ratios) (5.85, 95% CI [3.61, 9.49], P < .00001), ASA sensitivity (5.63, 95% CI [3.43, 9.23], P < .00001), allergic rhinitis (1.84, 95% CI [1.27, 2.67], P = .001) and asthma (3.15, 95% CI [2.61, 3.82], P < .00001) were found to be significantly associated with tissue eosinophilia. Atopy, however, was not significantly associated with tissue eosinophilia (1.71, 95% CI [0.59, 4.95], P = .32). Conclusion: Certain clinical disease characteristics such as ASA sensitivity, allergic rhinitis and asthma are more associated with CRS patients with eosinophilia when compared to those without eosinophilia. The phenotype of nasal polyps was also associated with ECRS. It is important for surgeons to recognise these comorbidities to ensure correct diagnoses, management and follow‐up are implemented.